LEVEL OF BIOSECURITY APPLICATION IN LAYER CHICKENS FARM IN BANGGAE TIMUR DISTRICT, MAJENE REGENCY - Hendro Sukoco; Rustang Rustang; Irma Susanti S; Siti Nuraliah; Suhartina Suhartina; Annisa Putri Cahyani; Suci Andanawari; Dahniar Dahniar; Ferbian Milas Siswanto (Agros Journal of Agriculture Science, 2023)
Biosecurity is something that greatly influences livestock production, especially in reducing the risk and consequences of the introduction of infectious diseases. Therefore, the implementation of biosecurity must be implemented well so that livestock are not easily affected by disease and can produce with good economic efficiency and achieve target production. The aim of this research is to determine the level of biosecurity implementation in layer chickens farms in East Banggae District. This research was carried out in East Banggae District, Majene Regency from August to October 2022 . This type of research uses quantitative descriptive analysis. The sample used in this research was 17 breeders. This research instrument uses a questionnaire whose contents are structured questions/statements, closed answer options using a measurement scale, namely the Guttman scale. The implementation of biosecurity observed in this research is isolation, sanitation and traffic control.  Data analysis in this research uses quantitative descriptive analysis. The results of this research show that the application of biosecurity is isolation with a percentage of 75%, sanitation with a percentage of 68.4%, and traffic control with a percentage of 22.2%. Keywords: Biosecurity, East Banggae, Layer Chickens, Majene